Great Flying Stories - Edited by Forsyth, Frederick (London Corgi Books, 1992)
A collection of flying stories featuring writers such as Frederick Forsyth, Sir Arthur Conan Doyle, Roald Dahl and Edgar Allan Poe. The styles used include science fiction, horror and detective fiction.
Keywords: Aeronautics -- Air pilots -- Short stories, American